2017
DOI: 10.1242/dmm.027847
|View full text |Cite
|
Sign up to set email alerts
|

Novel swine model of ricin-induced acute respiratory distress syndrome

Abstract: Pulmonary exposure to the plant toxin ricin leads to respiratory insufficiency and death. To date, in-depth study of acute respiratory distress syndrome (ARDS) following pulmonary exposure to toxins is hampered by the lack of an appropriate animal model. To this end, we established the pig as a large animal model for the comprehensive study of the multifarious clinical manifestations of pulmonary ricinosis. Here, we report for the first time, the monitoring of barometric whole body plethysmography for pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 53 publications
4
37
0
Order By: Relevance
“…At the clinical level, pulmonary exposure to ricin induces neutrophil influx to the lungs accompanied by a cytokine storm and the generation of a severe edema in the alveoli and pulmonary interstitium, which in turn leads to respiratory failure and death (11,35,44). Recently, we have shown that the clinical manifestations of ricin-induced respiratory damage in swine comply fully with the accepted diagnostic criteria for ARDS (18).…”
Section: Introductionmentioning
confidence: 73%
“…At the clinical level, pulmonary exposure to ricin induces neutrophil influx to the lungs accompanied by a cytokine storm and the generation of a severe edema in the alveoli and pulmonary interstitium, which in turn leads to respiratory failure and death (11,35,44). Recently, we have shown that the clinical manifestations of ricin-induced respiratory damage in swine comply fully with the accepted diagnostic criteria for ARDS (18).…”
Section: Introductionmentioning
confidence: 73%
“…In nonhuman primates (NHPs), inhalation of RT elicits the clinical equivalent of acute respiratory distress syndrome (ARDS), characterized by widespread apoptosis of alveolar macrophages, intraalveolar edema, neutrophilic infiltration, accumulation of proinflammatory cytokines, and fibrinous exudate (3)(4)(5). Similar effects are observed in mice, rats, and swine (6)(7)(8)(9)(10)(11). RT is derived from castor beans (Ricinus communis) and is a 65-kDa heterodimeric glycoprotein consisting of 2 subunits, RTA and RTB, joined via a single disulfide bond.…”
Section: Introductionmentioning
confidence: 91%
“…In addition to depurination-induced cell death and tissue damage, pulmonary ricin exposure results in a severe localized inflammation, associated with an intrapulmonary cytokine storm, massive neutrophil recruitment, and pulmonary edema, subsequently resulting in respiratory failure and death [ 3 , 11 , 12 ]. The clinical manifestation of ricin-induced respiratory damage in swine complies with the accepted diagnostic criteria for acute respiratory distress syndrome (ARDS) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%